Mechanical and electrical systems in buidings. - Tao, William K. Y., ....-; Janis, Richard, ....- (Upper Saddle River : Prentice Hall, 2001)
Samenvatting:A complete and practical introduction to the design of mechanical andelectrical systems in buildings. Features a large number of problems andapplications, chapters on communications, electrical design, and manyillustrations
Keywords: Elektrische installaties; Gebouwen; Gebouwinstallaties; Klimaatregelingsinstallatie